Problems of Law Enforcement Against Drug Users - Tiur Melia, Roslina; Azhali Siregar, Mhd. (PT. Multidisciplinary Press Indonesia, 2024)
The distribution and abuse of narcotics is one of the national problems that is considered serious by the government, because it can damage the nation's morals. Perpetrators of narcotics crimes often receive sentences based on court decisions that do not fulfill a sense of justice and legal certainty. In narcotics cases, there are several articles that are often used to ensnare perpetrators, namely Article 114, Article 112, and Article 127 of Law Number 35 of 2009 concerning Narcotics. Of the three articles, there are two articles that are open to multiple interpretations and unclear formulations, namely Article 112 and Article 127 of Law Number 35 of 2009 concerning Narcotics. The multi-interpretable articles will result in perpetrators of narcotics crimes (dealers) taking cover as if they were victims of narcotics crimes. That this will have an impact on the imposition of sentences with short sentences, thus causing injustice in the implementation process. This research is of a normative legal nature, namely a method that describes or explains a fact systematically, then the analysis is carried out legally by linking the data and facts obtained by analyzing court decisions relating to criminal sanctions against perpetrators of narcotics crimes and linked to applicable laws and regulations. The results of this study are that in this study, however, in the field of narcotics law enforcement, this seems to be much more difficult. Prioritizing criminal penalties seems to be very inherent in our law enforcement. Extraordinary encouragement is needed both at the local, national and international levels. So in relation to the case in this study, the Medan District Court Judge decided the defendant was legally and convincingly guilty in accordance with the provisions of Article 112 paragraph (1) of Law No. 35 of 2009 concerning Narcotics by sentencing the defendant Veri Suriana alias Veri to a prison sentence of 6 (six) years and a fine of Rp. 1,000,000,000, - (one billion rupiah) with the provision that if the fine is not paid, it must be replaced with a prison sentence of 6 (six) months.